2017
DOI: 10.1186/s12575-017-0065-2
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining RNA Integrity for Transcriptomic Profiling of Ex Vivo Cultured Limbal Epithelial Stem Cells after Fluorescence-Activated Cell Sorting (FACS)

Abstract: BackgroundTranscriptomic profiling of ex vivo cultured human limbal epithelial stem cells (hLESCs) will foster better understanding of corneal physiology and novel treatment paradigms to limbal stem cell deficiency (LSCD). However, currently such profiling studies are hampered due to difficulties with producing sufficient amounts of intact mRNA for deep RNA sequencing (RNA-seq) from subpopulations sorted on the basis of co-expression of membrane and intracellular antigens by fluorescence-activated cell sorting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Before sequencing, the RNA quality was analyzed using parameters described previously , and the values pertinent to individual populations are shown in Supporting Information Table S2. Although the RNA yield varied broadly, up to 2.8‐fold between the highest and lowest values, the RIN appeared consistent and sufficiently high (7.7 ± 0.4, n = 4) to meet the requirements of the protocol.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before sequencing, the RNA quality was analyzed using parameters described previously , and the values pertinent to individual populations are shown in Supporting Information Table S2. Although the RNA yield varied broadly, up to 2.8‐fold between the highest and lowest values, the RIN appeared consistent and sufficiently high (7.7 ± 0.4, n = 4) to meet the requirements of the protocol.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental set up was previously optimized to reveal markers pertinent to this study using a set of directly labeled antibodies and to determine the sorting thresholds using matching isotype controls for p63 and CK3 and fluorescence minus one (FMO) for ABCB5 . All buffers used in staining and subsequent FACS sorting were sPBS based, supplied with 50% Accumax (Sigma‐Aldrich) and 25 mM HEPES (Life Technologies) to prevent cell clumping and to maintain a proper pH range.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, antibodies against intracellular antigens were not tested since this necessitates cell fixation and/or permeabilization for FACS. However, others have reported that efficient RNA recovery from fixed cells may be feasible [3436]. Although most cells and biomaterials were fresh, our experiments did not control for age and variability in storage conditions, which may have affected our results.…”
Section: Discussionmentioning
confidence: 95%